Translation Of Cohesive Devices In Selected Legal Text Types From English Into Arabic - Mahamdeh, Ahmad Ali Hussain (2020)
Translation is a significant medium for transferring knowledge, culture, religion and innovations. It also becomes an inevitable channel to bridge the gap between a range of languages and cultures. With a wide spectrum of characteristics, translation depends on the text-type in order to determine the nature, behavior, characteristics and functionality of linguistic aspect. In legal translation, the language itself and its constituents such as cohesive devices are considered as sensitive and therefore make the translation a sensitive and difficult task which requires academic investigation to determine linguistic occurrences. This study handled the cohesive devices at the inter-sentential level. Thus, the present research adopts mixed method as a research design and it uses well-established theories of Halliday and Hasan (1976) on cohesion, Nida (1964) on translation techniques and Catford (1965) on translation shifts. The text-types examined are (a) operative legal texts: treaty, agreement and convention, and (b) handbook entitled, Handbook on Nuclear Law. The research reveals that most of the cohesive devices identified in the theory of Halliday and Hasan (1976) do occur in the operative legal texts and legal book. It is found that cohesive devices, translation techniques, translation shifts, frequency are determined by some language peculiarities and some language norm choices in translating legal texts from English language into Arabic language. The study recommends that other investigations should be done on the internal cohesion and external cohesion in legal text and other text-type.